Employee Recruitment and Selection - Isich, Sabina; Šikýř, Martin, 1974-; Němec, Otakar; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
The goal of the bachelor's thesis is to analyse the system of employee recruitment and selection in the company XY s.r.o. in the Czech Republic, to compare the theoretical approaches and applied practices, to define main strengths and weaknesses, and to propose the application of good practices as well as solutions to identified problems. The analyzed company XY s.r.o. is a subsidiary of a Russian international oil company that declined to be named. There is used a name XY in the bachelor's thesis. The theoretical part presents the concept of human resource management, specifies the process of staffing and defines the sources, criteria and methods of employee recruitment and selection. The practical part analyzes policies and practices of employee recruitment and selection in the company XY s.r.o. The bachelor's thesis is written based on literature, internal documents, interviews with employees and author's experience.
Vedoucí práce: Martin Šikýř
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses